2016
DOI: 10.1007/s12649-016-9526-0
|View full text |Cite
|
Sign up to set email alerts
|

Integral Valorization of the Water Hyacinth from the Canals of Xochimilco: Production of Edible Mushrooms and Forage

Abstract: Purpose This work assesses the feasibility of the valorization of water hyacinth, which grows in the canals of Xochimilco, México, through its use as substrate for the cultivation of edible mushrooms and forage. Methods Water hyacinth was processed using different pretreatments, producing four different substrates in which the mushroom was cultivated. The degradation of the substrate was estimated by its weight reduction, the biomass generation was measured, and the biological efficiency was calculated. The po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Among the products that aimed to produce in the composting of 83 articles identified, dominates the production of Organic Fertilizer (≈83%), followed by Anthropogenic soil (≈9%), Organomineral (≈5%), Pre-compost (≈2%) and Slurry (≈1%). Only 6 of the 83 researches did not used a source of organic material and/or additional mineral in composting process or after composting for production of their target product (Goyal et al, 2005;Chunkao et al 2012;Araiza et al, 2016;Martinez-Nieto et al, 2011;Packia Leksmi and Viveka, 2011;Sannigrahi and Chakrabortty, 2002).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the products that aimed to produce in the composting of 83 articles identified, dominates the production of Organic Fertilizer (≈83%), followed by Anthropogenic soil (≈9%), Organomineral (≈5%), Pre-compost (≈2%) and Slurry (≈1%). Only 6 of the 83 researches did not used a source of organic material and/or additional mineral in composting process or after composting for production of their target product (Goyal et al, 2005;Chunkao et al 2012;Araiza et al, 2016;Martinez-Nieto et al, 2011;Packia Leksmi and Viveka, 2011;Sannigrahi and Chakrabortty, 2002).…”
Section: Resultsmentioning
confidence: 99%
“…The most adopted macronutrients in monitoring are K, N and P, the latter two being, however, surpassed in organic carbon monitoring during/after composting, also significantly adopted in monitoring prior to composting. Is also adopted C/N ratio by a large number of the authors, and its prior monitoring to composting held to be maintained at close values to ideal for process and during/after composting verifying compost maturity (Araiza et al , 2016;Nath and Singh, 2016;Pushpa et al, 2016a;Bisen et al, 2017).…”
Section: Compost Monitoringmentioning
confidence: 99%
“…Moreover, WH could be transformed to a high-quality forage for animal feed. A previous study showed that the cultivation of edible mushrooms on WH biomass degrades almost all the lignincellulose of the substrate through enzymes, and enriches it with high protein content, making the spent substrate an excellent forage (Araiza et al, 2016).…”
Section: Valorization Of Whmentioning
confidence: 99%
“…Furthermore, the huge amount of WH biomass generates challenging waste management problems [1,2,[4][5][6]. Several studies have investigated different uses of WH as animal feed [7], fertilizer [7][8][9], a component in bioethanol production [10][11][12], an energy producer via combustion [13,14], or briquettes [15][16][17]. Nevertheless, these uses fail to consider the tendency of WH to fix heavy metals and other pollutants into its structure [18,19].…”
Section: Introductionmentioning
confidence: 99%